Dissipative heat transfer in Sisko fluid peristaltic flow through a cylindrical tube with nonlinear slip - Mehmood, Obaid Ullah (Begell House Inc., 2015)
We investigated the effects of dissipative heating on the Sisko fluid peristaltic flow in an axisymmetrically uniform cylindrical tube. Nonlinear velocity and thermal slip boundary conditions are employed with a constant tube wall temperature. Series solutions have been derived with the Sisko fluid parameter under a lubrication approach. Solutions for the stream function, axial pressure gradient, axial velocity, and the temperature and heat transfer coefficients are presented. Variations of several controlling parameters are graphically illustrated and discussed. Comparative profiles of temperature and heat transfer coefficients for Newtonian shear thinning and shear thickening fluids have been plotted and tabulated. A comparison with the existing study for a particular case appears to be in good agreement.